Integration of Islamic Values and Science in Islamic Primary Schools: A Philosophy of Science Approach - Dina Sutiana; Mulyawan Safwandy Nugraha (Journal of Elementary Education Research and Practice, 2025)
This research aims to analyze the integration of Islamic values and science in Islamic primary schools through a philosophy of science approach. The research identifies learning models that link science concepts with Islamic values, explores implementation challenges, and evaluates their impact on students' spiritual and intellectual character development. A qualitative approach with a case study method was applied in an Islamic primary school, with data collected through in-depth interviews with 6 informants. The findings show that the thematic-integrative model, Islamic scientific approach, and STEAM application based on Islamic values effectively integrate science concepts with the teachings of tawhid, ethics, and worship. These approaches enhance students' understanding of science and strengthen their spiritual awareness and critical thinking skills. Significant challenges include limited teacher competence in integrating Islamic and science knowledge, inadequate teaching facilities, and cultural resistance to integrative approaches. As solutions, the study recommends periodic teacher training, developing a philosophy of science-based learning modules, and collaborating with other Islamic education institutions. The study concludes that the philosophy of science approach supports the development of a relevant integrative curriculum capable of producing intellectually competent and spiritually grounded students with strong Islamic character to face the challenges of globalization.